A new tandem synthesis of bis(β, β′-dialkoxy carbonyl) compounds by oxidative cleavage of aziridines under metal-free conditions. Issue 3 (2nd January 2020) - Samanta, Satyajit; Santra, Sougata; Chatterjee, Rana; Majee, Adinath
Abstract : One-pot synthesis of bis(β, β′-dialkoxy carbonyl) derivatives has been reported by the oxidative cleavage of aziridines. Abstract : An efficient and new approach has been developed to synthesize bis(β, β′-dialkoxy carbonyl) derivatives through the reaction between N -tosylaziridines and malonate esters under ambient air using t BuOK in DMSO solvent. A plausible reaction pathway has been predicted. Control experiments suggested that the reactions proceed through the formation of α-aminoketones. This reaction offers a broad substrate scope, metal-free synthesis, excellent regioselectivity, easily accessible reactants, and simple operation. A gram-scale synthesis demonstrates the potential applications of the present method.